Extinction and the Human Four American Encounters. - Sweet, Timothy (Alembics: Penn Studies in Literature and Science Ser., 2021)
In Extinction and the Human Timothy Sweet ponders the realities of animal extinction and endangerment and the often divergent Native American and Euro-American narratives that surround them, focusing especially on the force of human impact on megafauna--mammoths, whales, and the North American bison.